Synthesis and characterization of new Oxazine , Thiazine and Pyrazol derived from chalcones (Baghdad Science Journal, 2025)
In this study, chalcones were synthesis by condensing 2-acetylpyridine with aromatic aldehyde derivatives in dilute ethanolic potassium hydroxide solution at room temperature according to Claisen-Schmidt condensation. After that, new heterocyclic derivatives such as Oxazine, Thiazine and Pyrazol were synthesis by reaction between chalcones with urea, thiourea and hydrazine hydrate respectively scheme 1. All these compounds wrer characterization by FTIR, 1H-NMR spectroscopy and elemental analysis.